Effective prevention of early resignation of newly graduated nurses: a transactional analysis - Masanori Ogawa; Ryusuke Ae; Teppei Sasahara; Keiko Omi (BMC, 2024)
Abstract Background New employees often exhibit stress reactions to changes in their environment and some of these may result in resignations. Employees in medical institutions are no exceptions. Considering the shortage of nurses in Japan, countermeasures are needed against the resignation of newly graduated nurses. Many studies have indicated that multifaced factors affect the resignation of newly graduated nurses. Even though individual characteristics are important factors in this regard, training and support for newly graduated nurses do not focus on the nurses' characteristics. The purpose of this study is to examine the characteristics influencing the early resignation of newly graduated nurses and suggest ways to support them and prevent their early resignation based on their characteristics. Methods With the approval of the Ethics Committee, various characteristics of 353 newly graduated nurses (personality, interpersonal relationships, trait anxiety, nurse orientation, desire to be a nurse, and self-proclaimed academic ability) were assessed using a transactional analysis, the State-Trait Anxiety Inventory, and self-reporting numerical rating scales. The characteristics of those who resigned within 1 year (case group) and those who did not (control group) were compared using chi-square test and logistic regression analysis. Results Our sample of 353 participants included 32 nurses from the case group and 304 nurses from the control group. Most participants showed similar personality traits. However, the control group had a significantly lower percentage with negative self, strong trait anxiety, negative self and strong trait anxiety, and low orientation compared to the case group. Our logistic regression analysis showed that strong trait anxiety and low nurse orientation are significantly related with the early resignation of nurses. Conclusions The early resignation of newly graduated nurses may be prevented by understanding their characteristics at the time of gaining employment and implementing early intervention programs, such as education programs to reduce anxiety, and helping those with strong trait anxiety and low nurse orientation to find meaning in work.